Association between hormone replacement therapy and carpal tunnel syndrome: a nationwide population-based study. Issue 1 (4th January 2022) - Tang, Hsien-Chin; Cheng, Ya-Yun; Guo, How-Ran
Abstract : Objective: Carpal tunnel syndrome (CTS) is the most common compressive focal mononeuropathy, and the increased incidence in postmenopausal and pregnant women suggests its association with oestrogen. The objective of this study is to evaluate the relationship between hormone replacement therapy (HRT) and the occurrence of CTS. Design: Population-based case-control study. Setting: Nationwide health insurance programme operated by the government with a near 100% coverage rate. Participants: We identified women ≥45 years old in the Health Insurance Research Database of Taiwan, which contains data on a representative sample of one million enrollees. After exclusion of those who were diagnosed with CTS before the prescription of HRT, a total of 118 309 participants were included and followed up for 15 years starting from 1 January 1996. Both HRT and occurrence of CTS were identified using the insurance claims. Main outcome measures: We identified incident patients of CTS and evaluated the association between HRT and CTS by calculating the OR. Results: Of the 4535 participants who developed CTS during the study period, 2334 (51.5%) were HRT recipients. In participants without CTS, the proportion of HRT recipients was 28.1%, yielding an OR of 2.72 with a 95% CI of 2.56 to 2.88. After adjustment for age, diabetes, rheumatoid arthritis, hypothyroidism, gout and obesity, the OR of CTS associated with HRT was 2.04 (95% CI 1.91 to 2.17). While HRT, diabetes, rheumatoid arthritis and gout had similar effects on CTS across all age groups, hypothyroidism and obesity had different effects on different groups. Conclusion: This study observed a positive association between HRT and CTS, independent of age, diabetes, rheumatoid arthritis, hypothyroidism, gout and obesity. While the ORs of CTS associated with HRT were similar across age groups, those associated with hypothyroidism and obesity were not, indicating effect modifications by age.